Afghanistan Economic Update, October 2014 - World Bank (Washington, DC, 2014)
Economic growth, down sharply in 2013 to 3.7 percent (estimated), has slowed further to 1.5 percent (projected) in 2014, from 9.4 percent per year during 2003-12. Uncertainty since 2013 over the political and security transition has been compounded by the protracted elections impasse in 2014. Investor and consumer confidence have slumped and led to a sharp reduction of new investment commitments in the non-agriculture sectors. Agricultural production has been robust in 2013-14, but flat from the record levels of 2012. Afghanistan faces a deteriorating fiscal crisis in 2014, with declining revenues leading to an unfinanced fiscal gap, depleted cash reserves, and accumulating arrears. Domestic revenues have continued to weaken, with the authorities anticipating revenues of Afs 105 billion ($1.82 billion) or 8.7 percent of GDP for fiscal 2014. This would represent a further decline from revenues of 9.7 percent of GDP in 2013, itself down from a peak of 11.6 percent in 2011. While the economic slowdown is part of the explanation, increasing weaknesses in tax and customs compliance are a large part of the problem. Even with austerity measures, the unfinanced fiscal gap is estimated at about $500 million for 2014. While part of this could be financed from cash balances, it is estimated that at least $300 million in additional financing will be needed for 2014 to cover civilian salaries, pensions, and critical operating and development spending. This will need to be accompanied by serious reforms to improve revenues. Addressing Afghanistan's formidable development challenges will require reforms in three areas: (i) restoring fiscal stability; (ii) restoring confidence and creating private-sector jobs; and (iii) strengthening social cohesion and service delivery. Above all, high level commitment to tackle corruption and strengthen governance across the board will be critical.